Safe and highly efficient adaptation of potentially explosive azide chemistry involved in the synthesis of Tamiflu using continuous-flow technology - Sagandira, Cloudius R.; Watts, Paul (Beilstein Journal of Organic Chemistry, 2019)
Tamiflu is one of the most effective anti-influenza drugs, which is currently manufactured by Hoffmann-La Roche from shikimic acid. Owing to its importance, more than 60 synthetic routes have been developed to date, however, most of the synthetic routes utilise the potentially hazardous azide chemistry making them not green, thus not amenable to easy scale up. Consequently, this study exclusively demonstrated safe and efficient handling of potentially explosive azide chemistry involved in a proposed Tamiflu route by taking advantage of the continuous-flow technology. The azide intermediates were safely synthesised in full conversions and >89% isolated yields.
Keywords: azide chemistry; continuous flow synthesis; hazardous; safe; Tamiflu